Efforts to Combat the Exploitation of Child Workers on Social Media From Community Law Perspective - Diny Widya Evriyanti Simarangkir (Universitas Negeri Semarang, 2026)
The development of digital technology and social media has significantly changed patterns of communication, social interaction, and economic activity. Besides providing benefits, social media also creates opportunities for the exploitation of children in forms increasingly complex and difficult to monitor. Children are not only users of social media but are also vulnerable to being used as objects of content commercialization, gaining popularity, and sources of economic profit for parties. This study aims to analyze the factors causing the exploitation of child workers on social media and efforts to address it from a community law perspective. The study employs a method using legal research through interviews, literature reviews, and documentation. Data were obtained from the Central Java DP3AKB, the Central Java UPTD PPA, and the Rumah Pejuang Keadilan Legal Aid Institute. The results indicate that the exploitation of children is influenced by poverty, low digital literacy, weak family supervision, permissive social culture toward child commercialization, and technological developments enabling anonymous and organized exploitation. From a community law perspective, effective child protection depends not only on regulations but also on legal culture and social awareness in protecting children’s rights in digital spaces. Mitigation efforts are carried out through strengthening regulations, digital monitoring, age restrictions on social media use, improving digital literacy, and involving families, communities, and digital platforms in creating child-friendly digital spaces. This research is also related to achieving SDG 4 on quality education and SDG 16 on child protection, social justice, and strengthening legal institutions in the digital era.